Self-efficacy and academic procrastination: a study conducted in university students of Metropolitan Lima - Arias-Chávez, D. (2020)
The objective of this study is to determine the relationship between self-efficacy and academic procrastination in university students of Metropolitan Lima, in the year 2019. The sample consisted of 712 subjects, including 344 male and 368 female subjects between the ages of 16 and 21 years old selected undertaking their first two terms at 7 private and public universities in the city of Metropolitan Lima. The sample was evaluated with the Specific Perceived Self-Efficacy Scale of Academic Situations (EAPESA) and with the Academic Procrastination Scale (EPA). Both instruments evidenced having psychometric properties of reliability, according to the internal consistency method, and construct validity through exploratory factor analysis. The results show that there is a relationship between self- efficacy and academic procrastination since Spearman’s correlation is -.139 and the effect size is 0.373. The statistical power is 1.00, so it is concluded that the results can be generalized to the entire population of university students in the city of Lima.